W-type normal dispersion thulium-doped fiber-based high-energy all-fiber femtosecond laser at 1.7 µm - Chen, Shaoxiang (2022)
We propose a parabolic W-type thulium-doped fiber for the 1.7 µm high-energy femtosecond pulsed laser. Despite its attractive normal dispersion, the fiber offers high gain in 1.7 µm region thanks to its distributed short-pass filtering effect. With a proper dispersion management in an all-fiber chirped pulse amplification (CPA) scheme, we demonstrate so far the highest pulse energy of 128.0 nJ in a stable pulse of 174 fs in the 1.7-1.8 µm region, which marks above an order of magnitude improvement in pulse energy while exhibiting the shortest pulse duration among fiber-based CPA works at 1.7 µm. Hence, we provide a pathway to an energy scalable and efficient femtosecond laser at 1.7 µm via a compact and elegant all-fiber solution.